E-Worksheet Text of Culinary Procedures to Achieve Writing Elements Competence Based on Prototype Curriculum - Mar’atus Sholihah; Sujinah; Eko Supriyanto; Tining Hariyanti (Journal of Pedagogy and Education Science, 2022)
The prototype curriculum is a curriculum that is derived from the improvement of the 2013 Curriculum. The prototype curriculum has learning outcomes that must be obtained by students in learning activities. These learning outcomes are classified in each subject. The division of classes based on the prototype curriculum into several phases, namely phase A for the elementary school level 1st and 2nd grade student, phase B for the elementary school level 3rd and 4th grade student, phase C for the elementary level of class th 5th and 6th grade student, phase D for the junior high school level, phase E for level 10th grade student of the high school, and phase F for 11th and 12th grade student of high school. The Indonesian learning in the prototype curriculum is in phase D for the junior high school level in which there are several elements, namely; listening, reading and listening, speaking and presenting, and writing. This study aims to describe the validity of e-worksheet teaching materials texts of Surabaya culinary procedures in terms of the feasibility of the material content and the feasibility of the media. To find out this, the teaching materials for the Surabaya e-worksheet text procedure are validated to material expert lecturers and media experts to find out the quality of the e-worksheet text of the Surabaya culinary procedure in terms of the feasibility of the content of the material and media. In this study, researchers use research and development methods. This study used the ADDIE development model. Data is collected by questionnaire techniques. Based on the results of the discussion, it can be concluded that the feasibility of e-worksheet text of Surabaya culinary procedures in terms of material gets an average percentage of 70% of the percentage interpreted in the decent category. furthermore, the feasibility of e-worksheet text of Surabaya culinary procedures in terms of media gets an average percentage of 91.25% or can be said to be very feasible.